Consumer perceptions of supermarket service quality: Scale development and validation - PF Venter; M Dhurup (South African Journal of Economic and Management Sciences, 2014)
The retail industry remains one of the largest sectors in the global economy. In South Africa, retailing is one of the toughest and most competitive industries. The South African retail business environment is becoming increasingly hostile and unforgiving, with intense competition from both domestic and foreign companies (Terblanche, 1998: 1). The findings of this preliminary study do provide basic support for a three-factor structure for supermarket service quality in terms of reliability and validity. The reliability analysis, which followed the factor analysis, reflected coefficient α values ranging from 0.85 to 0.90, indicating high internal consistency among variables within each dimension. In today's saturated retail markets, retailersface increasing hurdles to attract and maintain customers.